N‐[ω‐(Purin‐6‐yl)aminoalkanoyl] Derivatives of Chiral Heterocyclic Amines as Promising Anti‐Herpesvirus Agents. Issue 30 (26th July 2019) - Krasnov, Victor P.; Musiyak, Vera V.; Vozdvizhenskaya, Olga A.; Galegov, Georgiy A.; Andronova, Valeria L.; Gruzdev, Dmitry A.; Chulakov, Evgeny N.; Vigorov, Alexey Yu.; Ezhikova, Marina A.; Kodess, Mikhail I.; Levit, Galina L.; Charushin, Valery N.
Abstract : Novel conjugates of 2‐aminopurine and purine containing fragments of chiral heterocyclic amines attached at position 6 of purine core via a linker, fragment of omega‐amino acid, have been synthesized and evaluated in vitro for their anti‐herpetic activity in the Vero E6 cells; as a result, a new group of compounds possessing high inhibitory activity against herpes simplex virus type 1, including acyclovir‐resistant (TK – ) strain has been revealed. The anti‐herpetic activity of the synthesized compounds is substantially dependent on the stereo configuration of the fragment of heterocyclic amine. Abstract : Novel purine and 2‐aminopurine conjugates with chiral heterocyclic amines attached at C–6 via ω‐aminoalkanoyl fragment were synthesized. The obtained compounds exhibited inhibitory activity against both herpes simplex virus type 1 (HSV‐1) and acyclovir‐resistant HSV‐1 strains. Anti‐herpesvirus activity of the synthesized compounds depends on their stereo configuration.